Análisis del biocomercio en Colombia para pymes como oportunidad en mercados internacionales (2021)
This research work seeks to expose the concept of "bio trade" as an opportunity for small and medium-sized enterprises (Pyres) in Colombia, making a review of those first world countries and making a comparative and competitive analysis of Colombia with Peru, a country that promotes such activities in Latin America